Mapping the strategic management and organizational performance relationship - Nancy Priscilla Yunus; Suddin Lada; Ang, Hong Loong; Faerozh Madli (Penerbit UMS, 2022)
This study seeks to examine the relationship between strategic management and organizational performance using a comprehensive literature review and bibliometric analysis. The study attempted to record the intellectual structure, volume, and direction of knowledge development in a scientific manner. Data are extracted from Scopus datasets using Microsoft Excel and VOSviewer. Based on the vast amount of literature available, the researcher compiled an extensive database of 234 peer-reviewed publications published in the previous 10 years. Initial findings showed that, compared to the decade earlier to 2011, there have been significantly more publications on strategic management and organizational performance in the last 10 years. The most significant journals, authors, and articles on the topic were identified by the bibliometric analysis. This study demonstrates how a new topic can emerge and how it can offer fresh research directions in the vast field of strategic management. In addition, the developing field of business or company performance by combining the most crucial elements of organizational performance and strategic management into a single concept, such as “organizational performance”.